IMPLEMENTATION OF REGENT REGULATION NUMBER 29 OF 2024 ON THE PROCEDURES FOR THE COLLECTION OF NON-METAL AND ROCK MINERAL TAX FOR FISCAL YEAR 2024 IN BATU BARA REGENCY - Fadli, Muhammad; Jamaluddin, Yanhar; Sinaga, Rudi Salam (International Journal of Cultural and Social Science, 2026)
The implementation of Regent Regulation of Batu Bara Regency Number 29 of 2024 constitutes an important instrument in organizing the procedures for the collection of the Non-Metal and Rock Mineral Tax (MBLB) as one of the sources of Regional Original Revenue. This study aims to analyze the implementation of the regulation and to identify the factors influencing its effectiveness in the 2024 Fiscal Year. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation at the Regional Revenue Agency of Batu Bara Regency. Data analysis was conducted using the interactive model of Miles and Huberman. The analytical framework applies George C. Edwards III’s policy implementation theory, which consists of the variables of communication, resources, implementers’ disposition, and bureaucratic structure. The results indicate that the implementation of Regent Regulation Number 29 of 2024 has been carried out, but it has not yet been fully optimal. The aspects of communication and bureaucratic structure have functioned relatively well; however, limitations in personnel resources, weak supervision, low taxpayer compliance, and the prevalence of illegal mining remain major obstacles. The disposition of implementers generally shows good commitment, but it has not been fully supported by adequate systems and facilities. Therefore, strengthening coordination, improving the capacity of personnel, and enhancing supervision and data collection systems are key measures to optimize MBLB tax revenue in Batu Bara Regency.